The influence of increased water temperature on the duration of spermatogenesis in a neotropical fish, Astyanax altiparanae (Characiformes, Characidae) - Postingel Quirino, Patricia [UNESP]; da Silva Rodrigues, Maira [UNESP]; da Silva Cabral, Elis Marina [UNESP]; de Siqueira-Silva, Diógenes Henrique; Mori, Ricardo Hideo [UNESP]; Butzge, Arno Juliano [UNESP]; Nóbrega, Rafael Henrique [UNESP]; Ninhaus-Silveira, Alexandre [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP] (Springer Nature, 2020)
In view of the established climate change scenario and the consequent changes in global temperature, it is essential to study its effects on animal spermatogenesis. Therefore, the aim of this study was to verify the duration of spermatogenesis at different temperatures. For this purpose, 96 male and adult specimens of Astyanax altiparanae were kept in a closed circulation system with water temperature stabilized at 27 °C and 32 °C. Subsequently, the specimens received pulses of BrdU (bromodeoxyuridine) at a concentration of 100 mg/kg/day for 2 consecutive days, and the samples were collected daily for a period of 15 days. Their testes were removed, fixed, processed in historesin, and sectioned in 3 μm, submitted to hematoxylin/eosin staining and to bromodeoxyuridine immunodetection. Partial results of the optimum temperature experiments allowed the classification of A. altiparanae spermatogenic cells in Aund, Adiff, and type B spermatogonia, spermatocytes, spermatids, and spermatozoa. The duration of spermatogenesis was determined as approximately 6 days for animals at a temperature of 27 °C and 1 day for animals at 32 °C. The elevated temperature was also responsible for increasing cell proliferation, resulting in an increase in the number of spermatocytes, spermatids, spermatozoa, and cell death (cell pyknotic). The duration of spermatogenesis in A. altiparanae was directly affected by the elevated water temperature, causing a reduction in the estimated time of spermatogenesis.
Keywords: Bromodeoxyuridine; Characiformes; Reproduction; Yellow-Tetra